Comparison of ketamine and propofol as maintenance agent for continuous intravenous infusion anaesthesia in water buffaloes - MALIK, V; KINJAVDEKAR, P; AMARPAL, AMARPAL; AITHAL, H P (The Indian Journal of Animal Sciences, 2012)
The present study was conducted to compare the anaesthetic effects of ketamine and propofol as maintenance agents for continuous intravenous infusion anaesthesia in buffaloes. Clinically healthy adult male buffaloes (6), 2 to 3 year-old and weighing 290 to 325 kg, were used for repeated trials in 2 groups using medetomidine (2.5µg/kg) and butorphanol (0.05 mg/kg) intravenously as preanaesthetics. Induction of anaesthesia was achieved with 5% thiopental sodium in both groups. Anaesthesia was maintained with continuous intravenous infusion of ketamine (1%) in group K and propofol (1%) in group P. The treatments were compared by clinicophysiological, cardiorespiratory and haemodynamic parameters. Excellent sedation, analgesia and muscular relaxation were observed in both groups. Depression of palpebral and corneal reflex was higher in group P than in group K. Downward rotation of eye ball for longer time was observed in group P than in K group. Required mean infusion rates of ketamine and propofol to maintain the adequate depth of anaesthesia in groups K and P were 0.16±0.01 mg/kg/min and 0.05±0.00 mg/kg/min, respectively. The values of recovery time, sternal recumbency time and standing time did not differ significantly between the groups. Difference in heart rate was not significant up to 60 min of anaesthesia but after 70 min onwards HR in group K was significantly higher compared to groups P. Respiratory rate in groups K remained significantly higher during the maintenance period than in group P. Decrease in rectal temperature was significantly higher in group P than in K group. Mean arterial pressure in groups K remained significantly lower than in group P. Central venous pressure did not differ significantly between the groups. Haemoglobin oxygen saturation (SpO2) in group P remained significantly higher than in group K. Our results indicated that maintaining anaesthesia via continuous infusion of ketamine and propofol in buffaloes is a feasible, effective, and safe anaesthetic technique for surgical procedures of at least up to 2 h duration. Maintaining anaesthesia with propofol produced some depressive effects on cardiopulmonary parameters that were comparable to those associated with anaesthesia maintained by ketamine.